Nucleophilic aromatic amination and hydroalkylation of styrenes with alkyl amines mediated by alkali metal hydrides - Pang, Jia Hao (Nanyang Technological University, 2022)
The alkali metal hydrides are one of the most widely used Brønsted bases in synthetic chemistry. Our group has recently discovered that solvothermal treatment of sodium hydride with various dissolving iodide salts in THF imparts both a unique hydridic reactivity and an significant increase in its Brønsted basicity to sodium hydride. The resulting sodium hydride-iodide composite is capable of deprotonative metalations on less acidic aliphatic amines (pKa of H2 = 36, pKa of pyrrolidine = 44), directed sodiation of arenes, hydride reduction of various π-polar electrophiles and hydrodehalogenation of haloarenes. The thesis describes the utilization of readily available sodium and potassium hydrides as bases for generation of alkali metal amide anions and their nucleophilic addition reactions. Chapter 1 provides an overview on the methods for the generation of sodium and potassium organometallic compounds from organic molecules. The chapter is divided into two sections, the first section focuses on the state-of-the-art reagents available for metalations of organic molecules, whereas the second section focuses on the generation of sodium/potassium organometallic compounds from sodium/potassium hydride and the use of activated sodium/potassium hydride for reductive transformations. Chapter 2 will describe the nucleophilic aromatic substitution of methoxypyridines using sodium alkylamides generated from alkylamines and sodium hydride-iodide composite. The reaction was able to effect amination at the C3 position of pyridines which was rarely achieved by the conventional methods without using transition metals. Chapter 3 demonstrates the utility of the NaH/LiI composite in the Chichibabin amination of pyridines for the synthesis of C-2 aminated pyridines. This protocol showed higher process efficiency with wider substrate scope under milder reaction conditions over the traditional Chichibabin amination. Chapter 4 describes the selective hydroalkylation of styrenes with benzylamines mediated by potassium hydride. The use of heavier counter cations on the amide anions is found to be the key in influencing the selectivity switch from conventional hydroamination to unusual hydroalkylation via reversible 1,2-anion shift from the amide anion to the benzylic carbanion. Chapter 5 lists the experimental data for the respective chapter 2, 3 and 4. Chapter 6 gives a conclusion and summary to thesis.